The 'new one' - a pest personified - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
The pest from Afar 11pp published by GTZ, PO Box 5180, 65726 Eschborn, GERMANY